Cutting the flow: Argentina as a success case against drug trafficking 2016–2019 - Verrier, Martin (Journal of illicit economies and development, 2020)
Three Latin American countries centralise cocaine production in the world: Bolivia, Peru, and Colombia. However, the leading consumer markets are the United States and Europe. Transna- tional organised crime often dispatches shipments directly from producing countries, but also often use transhipment countries as a strategy to reduce risks. Argentina was for many years identified as an essential cocaine transhipment country especially bound to Europe. This phenomenon gave place to the consolidation of an internal cocaine market that had a profound impact on crime levels in the country. In December 2015, a new strategy to counter drug trafficking was introduced, based on sev- eral institutional strengthening programs divided on four pillars aimed at raising operating costs and risks for criminal organisations. This strategy included policies aimed at reducing the supply of drugs, generating an environ- ment hostile to organised crime, reducing demand, and improving control of money laundering by these organisations. While the natural illegal characteristic of this market makes it difficult to estimate the outcome of this strategy, it is possible to state that Argentina went through an institutional strengthening process that appears to have at least affected the transhipment of cocaine to Europe. Other impacts remain to be confirmed through further studies